Agricultural land lease in Professor Aleksander Lichorowicz’s works - Suchoń, Aneta (Przegląd Prawa Rolnego, 2024)
The article is an attempt to present selected theses formulated by Professor Aleksander Lichorowicz and look at them in the context of contemporary challenges and discussion on the need to change the legal regulations, which is a task now vested in a team appointed to draft a law on agricultural lease. Accordingly, after the characterisation of a lease from the point of view of contemporary challenges, Professor Lichorowicz’s basic theses on lease are presented, followed by some de lege ferenda conclusions referring to the draft lease regulation of 2015, in the elaboration of which Aleksander Lichorowicz had also participated. In the conclusion it is emphasised that the conducted deliberations confirm that the scientific output of Professor Lichorowicz concerning lease is extremely rich and timeless. It constitutes a source of inspiration for science, legislature and practice. Particularly important are the legal and comparative studies.